Rethinking the masters of comparative law - Riles, Annelise (Hart Pub., 2001)
Comparative Law is experiencing something of a renaissance, as legal scholars and practitioners traditionally outside the discipline find it newly relevant in projects such as constitution and code drafting, the harmonization of laws, court decisions, or as a tool for understanding the globalization of legal institutions. On the other hand, comparativists within the discipline find themselves asking questions about the identity of comparative law, what it is that makes comparative law unique as a discipline, what is the way forward. This book, designed with courses in comparative law as well as.